How does the burial rate control the diagenesis of sandstone? Insights from a diagenetic physical simulation experiment - Chen, Sirui; Xian, Benzhong; Ji, Youliang; Li, Jiaqi; Rahman, Naveed Ur; Tian, Rongheng; Wang, Pengyu (Chemical geology, 2024)
The study conducted physical simulation experiments on sandstone samples from the Junggar Basin to investigate how burial rates influence sandstone diagenesis and reservoir quality. Results show that the mechanical compaction under a negative burial rate (tectonic uplift) almost stops to destroy the sandstone reservoir space, the capacity of fluid seepage is the strongest and the sandstone tends to develop ‘weak compaction–strong dissolution’ diagenetic facies. For positive burial rates, sandstones with a low burial rate tend to develop ‘medium compaction–medium dissolution’ diagenetic facies; sandstones at a medium burial rate easily form ‘strong compaction–weak dissolution’ diagenetic facies, and sandstones at a high burial rate tend to develop ‘weak compaction–weak dissolution’ diagenetic facies. Experimental results indicate that the compaction strength and damage to sandstone reservoirs may not consistently rise with the burial rate. Faster burial rates do not always intensify compaction; the degree of compaction depends on fluid overpressure. If the increase in burial rate does not induce the fluid overpressure in sandstones, the burial rate is higher and the destruction degree of primary pores caused by mechanical compaction is greater; mechanical compaction also simultaneously causes the diagenetic system to be more closed and the dissolution to be weaker. If the increase in burial rate can induce the fluid overpressure in sandstones, the burial rate is higher, the inhibition of mechanical compaction by fluid overpressure is more pronounced. However, fluid overpressure also strengthens the closure of the diagenetic system, hindering the injection of external acidic fluids into the sandstone, which is not conducive to dissolution. Overall, low burial rates with normal pressure favour secondary pore development, high burial rates with overpressure preserve primary pores, while medium burial rates with normal pressure are unfavourable for primary and secondary pores.